#TITLE_ALTERNATIVE# - HADI WIYONO (NIM: 22412305); Pembimbing : Dr. Andri Dian Nugraha, SAMSUL
Deformation that occurs in the earth's surface can be determined directly by geodetic measurements and tectonic analysis. However, the deformation that occurs in the mantle can only be identified using seismic anisotropy. The use of S wave in determining the seismic anisotropy in upper mantle is quite reasonable, since the S wave is polarized into two mutually perpendicular components when entering an anisotropy medium. In this study, we analyzed as many as 115 teleseismic events with the epicentre distance between 90° to 140° from seismic stations which are located in West and East Nusa Tenggara during recording period from 1 January 2010 until 30 June 2014. XKS phases used in this analysis are mainly caused by the earthquake with magnitude M>6,0. Based on the analysis of seismic anisotropy using shear wave splitting method, we produced as many as 700 pairs of splitting parameters from 14 observation stations. From this study, we obtained an average of time delay for each station ~ 2.0 seconds that is associated with originating of seismic anisotropy from below the slab rather than on top. Moreover, the fast polarization direction of the S wave which is coherent to the absolute plate motion within the hotspot frame could be interpreted as the present mantle deformation that has similar direction with crustal deformation that occurs in the Earth's surface. In addition to splitting parameters, we also obtained the null measurements which can be interpreted as the effect of two-layers anisotropy perpendicular to the polarization direction of the fast component, the distance between seismic stations to the trench is greater than 100 km which effectively contribute to the small delay time and null results, a very complicated structure anisotropy or may also be caused by the initial polarization angle of S waves that are parallel or perpendicular to the polarization angle of fast component.